The style and subject of the contemporary Islamic painting in Malaysia of the 80’s and 90’s / Ahmadrashidi Hasan, Azian Md. Zain and Abd. Rasid Ismail - Hasan, Ahmadrashidi; Md. Zain, Azian; Ismail, Abd. Rasid (2005)
This study was carried out with the purpose to investigate the progress and development of art in Malaysia, in particular the Islamic art. The decades of 80s and 90s appeared to be the period of Islamic art resurgence and this study was designed to find out the fact about the resurgence and the influencing factors. The study entailed about the Islamic substance, interest, and the Islamic manifestations of the artworks. Islamic art turn out to be a mainstream ill the development of the Malaysian modem art in the 80s and 90s. This is an important occurrence and should be recorded as a historical fact and as document of reference in the future. An observation employing Content Analysis method was carried out to analyse the form and content of the samples. A method of Islamic art analysis method was concluded. 83 samples were collected by using the judgmental sampling methods from a population of 320 artworks of the 80s and 90s created by Muslim artists. Interviews were carried out employing art historian and artists as respondents to collect additional and supportive data regarding development of art in Malaysia. Findings established that decades of the 80s and 90s as the decades of resurgence of Islamic art. The resurgence in art was the result of the Islamic resurgence in Malaysia started with the Malayan nationalism movements before the independence, followed by the drastic government effort in advancing Islamic state of affairs after the independence. The resurgence of Islamic art, in particular, was owing to the role played and effort performed by FSSR, UiTM. Findings established that there is no significant style that could be categorized as style of Islamic art and Islamic art could be expressed in various styles as long as it abided by the Islamic law (Syariah) or jurisprudence (fqih). The Islamic manifestations of Islamic art were expressed in 3 approaches i.e. The Obvious Islamic Manifestations, The Hidden Islamic Manifestations, and Exclusive of Islamic Manifestations. These expressions could be perceived through the employment of the title, images and motifs, and the content or meaning of the samples.